Cosmological direct-collapse black hole formation sites hostile for their growth. Issue 1 (13th January 2021) - Chon, Sunmyon; Hosokawa, Takashi; Omukai, Kazuyuki
ABSTRACT: The direct collapse (DC) is a promising mechanism that provides massive seed black holes (BHs) with ∼10 5 M⊙ in the early universe. To study a long-term accretion growth of a direct-collapse black hole (DCBH), we perform cosmological radiation-hydrodynamics simulations, extending our previous work where we investigated its formation stage. With a high spatial resolution down below the Bondi radius, we show that the accretion rate on to the BH is far below the Eddington value. Such slow mass growth is partly because of the strong radiative feedback from the accreting BH to the surrounding dense gas. Even after it falls into the first galaxy, the accretion rate is substantially suppressed due to the supernova feedback associated with the intense star formation. Moreover, the BH has a large velocity of ∼100 km s −1 relative to the gas, which further reduces the accretion rate. This large relative velocity stems from the fact that the DCBHs form in metal-free environments typically at ∼1 kpc from the galaxy. The BH accelerates as it approaches the galactic centre due to the gravity. The relative velocity never damps and the BH wanders around the outer galactic region. An analytic estimate predicts that the DCBH formation within ∼100 pc around the galactic centre is necessary to decelerate the BH with dynamical friction before z = 7. Since metal enrichment with Z ∼ 10 −5 −10 −3 Z ⊙ is expected there, the formation of DCBHs in the metal-enriched environments is preferable for the subsequent rapid growth.